Allocation of environmental costs in enterprises of chemical industry - Hyršlová, Jaroslava (Univerzita Pardubice, 2002)
Allocation of environmental costs to appropriate product, department (production centre), or activity (process) is highly significant for managerial decision making. The knowledge of environmental costs and their transparency represent starting data for a lasting evaluation of the efficiency of products, production centres and processes and for responsible planning of products and activities. The paper shows and compares different approaches to allocation of environmental costs in enterprises of chemical industry.
Keywords: chemický průmysl; Životní prostředí; náklady na životní prostředí; environmentální management